The impact of artificial intelligence on the development of communicative marketing - Voloshko, Liudmyla (Global Prosperity, 2026)
Abstract. The article is devoted to the study of the impact of artificial intelligence on the transformation of marketing communications, changes in instrumental support, the logic of managerial decision-making and the formation of new approaches to building communication strategies in the digital environment. The purpose of the article is a comprehensive analysis of the impact of artificial intelligence on modern marketing communications. To achieve the goal, methods of analysis, synthesis, comparison, generalization, systematization and a structural-functional approach were used. The results of the analysis allowed us to clarify the modern content of marketing communications in the context of digital transformation and outline the practical possibilities of integrating intelligent technologies into the activities of companies. The scientific novelty lies in the systematization of artificial intelligence tools relevant for 2026, which are already actually used in marketing practice and have applied value for communications management, analytics and process automation. In the study, the author has collected, based on expert literature, the prospects for the further development of artificial intelligence and presented them taking into account the risks and obstacles that businesses will encounter at the stage of AI integration. All this together forms a practical significance, which consists in analyzing the use of specific programs and applications for various marketing purposes, in particular for analytics and forecasting, content generation, social network management, personalization of client interactions, optimization of advertising campaigns and monitoring of brand reputation. The results obtained can be used to improve the effectiveness of the development and implementation of marketing communication strategies in the business environment.